2023
DOI: 10.1111/1747-0080.12812
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐method study to inform the development and implementation of eHealth in a bariatric surgery service in an Australian public hospital

Abstract: AimThis study aimed to explore patient barriers to accessing services, current technology ownership/use and digital device preferences for accessing health information/health service delivery. Additionally, it aimed to explore the Theoretical Domains Framework and the acceptability of future eHealth solutions in bariatric surgery.MethodsThis mixed‐method study (survey and semi‐structured interviews) was conducted in a bariatric surgery service in an Australian public hospital. Quantitative data were analysed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…This relationship may be attributed to increased costs, both in terms of money and time. E-health technologies such as telemedicine, web-based media, smartphone apps, and wearables can help overcome this barrier [ 30 , 31 ]. Smoking patients were less likely to attend appointments compared to non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship may be attributed to increased costs, both in terms of money and time. E-health technologies such as telemedicine, web-based media, smartphone apps, and wearables can help overcome this barrier [ 30 , 31 ]. Smoking patients were less likely to attend appointments compared to non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, a mixed-methods approach was adopted to gain further insight from adults undergoing bariatric surgery regarding their barriers to accessing bariatric surgery services, and to explore unmet patient needs, technology use, and digital device preferences, which has been previously published. Knowledge of the barriers to accessing bariatric surgery services further validated the integration of mHealth interventions within the perioperative pathway, and modalities such as text messaging and emails offering additional support, information, and resources regarding diet and physical activity were recommended [ 18 ]. In addition, the selection of behaviour change techniques was informed by systematic literature reviews [ 18 , 28 ] and a matrix that mapped behaviour change techniques to the theoretical domains (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Lauti et al conducted a randomised controlled trial with patients following laparoscopic sleeve gastrectomy and found text message support is feasible, may reduce weight regain, and is valued [ 17 ]. While bariatric surgery patients have a preference for text messaging, they also report a desire for email approaches and want additional postoperative support, information, and resources from their bariatric surgery health service [ 18 ]. It seems warranted therefore that further evaluation of an intervention using multiple digital strategies is undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the iPhone was launched by Apple Inc and was transformational in how we communicate with each other, and after the advent of apps, has changed our professional, educational, financial and leisure behaviours. In this issue of Nutrition & Dietetics , there are articles from dietitians researching and employing communication and information technologies in their research and practice 1–5 …”
mentioning
confidence: 99%
“…Diverse groups of people may benefit from dietitians developing electronic and mHealth services. Wright and colleagues have undertaken exploratory research examining bariatric patients' barriers to accessing dietetics services and their preferences for digital delivery using mixed methods research 4 . This study reports that text messages and emails were preferred modalities for information.…”
mentioning
confidence: 99%